Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Section 8.3 - Polynomial and Rational Functions - Exercise Set - Page 595: 33



Work Step by Step

g(x)=$\frac{x^{2}+2x}{x+3}$ g(-6)=$\frac{(-6)^{2}+2(-6)}{-6+3}$= g(-6)=$\frac{36-12}{-3}$=$\frac{24}{-3}$=-8
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.